ANALISIS KESALAHAN PESERTA DIDIK DALAM MENYELESAIKAN SOAL KONEKSI MATEMATIS BERLANDASKAN ANALISIS KESALAHAN NEWMAN DI KELAS VII MTsN 1 PADANG - Ananda, Elsa Riski (Jurnal Edukasi dan Penelitian Matematika, 2023)
Mathematical connection ability is defined as a skill that is needed when learning mathematics, in fact, class VII students of MTsN 1 Padang who make mistakes when working on mathematical connection problems. For this reason, an analysis of student errors was carried out in solving mathematical connection problems. This study aims to describe the mistakes made by class VII students of MTsN 1 Padang in solving mathematical connection problems based on Newman's error analysis. The type of research used in this study was descriptive research with a qualitative approach with 6 research subjects selected based on high, medium and low skills. For each skill, 2 students were selected based on variations in answers. The results showed that the types of errors made by class VII students of MTsN 1 Padang in solving mathematical connection questions based on Newman's error analysis consisted of 31% reading errors, 25% understanding errors, 52% transformation errors, 52% processing skills errors. by 62%, and wrong in writing the final answer by 61%.Keywords– Analysis of Student Errors, Newman’s Error Analysis, Mathematical Connection Ability.